Association of polymorphisms of zinc metalloproteinases with clinical response to stem cell therapy - Panovsky, R; Vasku, A; Meluzin, J; Kaminek, M; Mayer, J; Janousek, S; Kincl, V; Groch, L; Navratil, M (Herz, 2010)
AIM: The purpose of this study was to assess the associations of polymorphisms in two metalloproteinase genes-metalloproteinase-2 (MMP-2) and angiotensin converting enzyme (ACE)-with clinical response to autologous transplantation of mononuclear bone marrow cells (MBMC) in patients with acute myocardial infarction. METHODS: The double centre study included 48 patients with a first acute myocardial infarction treated with primary coronary angioplasty, stent implantation and transplantation of MBMC. According to the changes in perfusion defect size, left ventricle ejection fraction, end-systolic volume and peak systolic velocity of the infracted wall (dSaMI) after cell therapy, the patients were retrospectively divided into group A (responders) and group B (non-responders). Genomic DNA was isolated from peripheral leukocytes by a standard technique using proteinase K. Three MMP-2 promoter (-1575G/A, -1306C/T and -790T/G) as well as I/D ACE gene polymorphisms were detected by PCR methods with restriction analyses (when necessary) according to standard protocols. RESULTS: Of the 48 patients who received MBMC transplantation, 17 responded to the therapy. There were no significant differences in the prevalence of matrix metalloproteinase-2 triple genotype GGCCTT between responder/non-responder groups (71% versus 61%, p=0.375). Similarly, no differences in either genotype distribution or allelic frequencies of I/D ACE polymorphism between responders and non-responders to the cell therapy were observed (p=0.933). Compared to patients with ACE genotype ID or DD, the patients with ACE II genotype significantly improved in regional systolic LV function of the infarcted wall after implantations of MBMC (dSaMI - 0.4 versus 1.4 cm/s, p=0.037). CONCLUSION: In our study, the ACE genotype II was associated with improvement of regional systolic LV function of the infarcted wall after implantations of MBMC. The detected polymorphism in matrix metalloproteinase-2 gene was not associated with clinical response to cell therapy.
Keywords: Promoter Regions, Genetic; alely; angiotensin konvertující enzym; Humans; Polymerase Chain Reaction; Gene Frequency; Genotype; Matrix Metalloproteinase 2; Myocardial Contraction; Cell Count; funkce levé komory srdeční; stenty; Polymorphism, Genetic; polymorfismus genetický; Peptidyl-Dipeptidase A; transplantace kostní dřeně; promotorové oblasti (genetika); Bone Marrow Transplantation; polymerázová řetězová reakce; Myocardial Infarction; Stents; frekvence genu; matrixová metaloproteinasa 2; infarkt myokardu; genotyp; lidé; počet buněk; Ventricular Function, Left; kontrakce myokardu; Alleles